Strengths-based approaches to disability, the supports paradigm, and the importance of the supports intensity scales - Wehmeyer, Michael (Revista Educação Especial, 2020)
Historically, disability has been conceptualized within deficits-based models. But, newer models that emphasize the fit between health, the environment, and personal factors are leading to strengths-based approaches to supporting people with disabilities. This article explores implications for such models on disability, in general, and special education, specifically. The importance of self-determination to operationalizing such models is discussed. Finally, the shift to a supports paradigm as part of the response to person-environment fit models is examined, along with a discussion pertaining to a series of measures of support needs.